Social resilience and long-term adaptation to volcanic disasters: The archaeology of continuity and innovation in the Willaumez Peninsula, Papua New Guinea. (11th February 2016) - Torrence, Robin
Abstract: A review of archaeological research on the impacts of multiple volcanic events in the Willaumez Peninsula, Papua New Guinea during the past 40, 000 years demonstrates that disaster studies in archaeology would benefit from considering resilience and innovation in addition to the more common emphasis on vulnerability, often glossed as 'collapse.' When analytical time frames are extended beyond the immediate environmental impacts, continuity in cultural practices is often observed. The long-term exchange of obsidian in the Willaumez Peninsula may have been adaptive because the resulting social ties enabled impacted populations to find refuge with other communities. In contrast, a series of novelties were much less resilient. A hypothetical reconstruction of cultural responses to the high magnitude W-K2 volcanic event is used to illustrate how disasters can provide opportunities for innovative behavior leading to culture change.